Usıng ARIMA to Forecast Cryptocurrency Prıces - Ketan Shelke, Aniket Sabale, Piyush Chauhan, Yuvraj Yeole (International Journal of Advanced Science and Technology, 2020)
Cryptocurrency has fascinated young and old alike. People either love it or hate it, but they cannot ignore it. While some are confused about whether it is a safe investment, there are others who have made millions selling it. For a digital currency that started out with 1 and reached a peak of 18,000 in 2017, it is important from an academic point of view to study the phenomenon and check whether traditional forecasting methods such as ARIMA can be used to forecast its future prices. The use of ARIMA will prove beneficial to predict the future prices of the various cryptocurrencies available and will go on to arm investors in making better financial decisions. It will also help us check whether such tools are indeed capable of predicting the prices and the accuracy of the predictions. Output from the exercise can help future researchers gain insights into the process and help in the refining of the prediction. The study also takes past researches into account to better the process of forecasting and use as much data available to be fed to the program. EViews software has been used to do the ARIMA programming.